Effectiveness of breast acupressure towards increasing breastmilk production in postpartum mothers: a systematic literature review - Dian Monalisa; Yuni Kusmiyati; Mahindria Vici Virahaju; Heru Subaris Kasjono; Bima Suryantara (Jurnal Kesehatan Ibu dan Anak, 2022)
Breast Milk is an emulsion of fat in a solution of protein, lactose and inorganic salts secreted by the mammary glands which is useful as baby food. According to the 2019 Indonesian Health Demographic Survey, the achievement of exclusive breastfeeding in Indonesia was 61.33%, but not all babies were breastfed on the first day until the third day. Efforts to increase breast milk production can be done through pharmacology and non-pharmacological therapies. Pharmacological therapy can be performed by consuming breast-feeding drugs, non-pharmacological therapy can be performed by providing breast acupressure. This study aim to find out the intervention procedures, the benefits of breast acupressure intervention on the increase in breast milk production. This was a systematic literature review. Literature searching conducted for articles used electronic databases of Science Direct, Pubmed, Google Scholar, and Scopus. Articles that met the inclusion criteria were further analyzed systematically. Based on the systematic review on 10 selected article, it was explained that breast acupressure could help increase breast milk production among postpartum women. Breast acupressure could help increase breast milk production among postpartum women.